Emotional Distress in Cancer Patients During the First Wave of the COVID-19 Pandemic - Toquero, Patricia; Blanco Fernández, Carmen; López Martí, María Pilar; Hernández Marín, Berta; Vera Cea, E. Beatriz; Garrido García, Ana; Méndez Carrascosa, Elena; Bañón Torres, Dulce; Donnay Candil, Olga; Ballesteros García, Ana Isabel; Sánchez-Torres, José Miguel; Costas Rojo, Pablo; et al. (Frontiers in Psychology, 2021)
Background: The COVID-19 pandemic has caused mental health problems worldwide. The psychopathological implications of COVID-19 in cancer patients have rarely been addressed. Considering the increased vulnerability of oncology patients, this issue needs to be addressed to improve the long-term mental health status of these patients. Methods: we conducted a prospective study in outpatients under active cancer treatment during the first wave of the COVID-19 pandemic. A semi-structured 24-question survey was designed to measure baseline sociodemographic, psychosocial and COVID-19 exposure characteristics. The Hospital Anxiety and Depression Scale was used to measure psychological symptoms. A descriptive and analytical univariate analysis of the variables studied was performed. We used the Z-score to compare different populations (experimental and historical control cohort). Results: 104 patients were included, the majority of which were women (64.4%), were above 65 years of age (57.7%), had either lung and breast cancer (56.7%), had advanced disease (64%) and were undergoing chemotherapy (63.5%). 51% of them expressed greater fear of cancer than of COVID-19 infection or both. In relation to HADS, 52.8% of emotional distress, 42.3% of anxiety and 58.6% of depression rates were detected. The main factors related with higher rates of psychological symptomatology were history of previous psychotropic drug consumption and the adoption of additional infection prevention measures because they considered themselves at risk of severe COVID-19 infection (p=0.008; p=0.003 for emotional distress, p=0.026; p=0.004 for anxiety, and p=0.013; p=0.008 for depression). Tumor type, stage, oncologic treatment or rescheduling of cancer treatments were not related to higher levels of psychological symptomatology. Comparison of our results with another population of similar characteristics was not significant (Z score = -1.88; p=0.060). Conclusions: we detected high rates of emotional distress during the first wave of the COVID-19 pandemic among cancer patients in active treatment (52.8%). This was higher and clinically relevant than observed in a comparable population (42.5%), although not significant. Cancer itself is the main factor of concern for cancer patients, above and beyond the emotional distress generated by COVID-19 pandemic.